Evaluation of matrix metalloproteinases(MMP-8, -9) in pregnant women attending Hospital USM - Rehman, Sarmed Saif-Ur (2020)
Pregnancy increases the propensity to periodontal inflammation, which includes an enhanced gingival bleeding tendency without specific plaque association, periodontal pocket depth (PPD) and clinical attachment loss (CAL). These pregnancy-related periodontal changes, however, seem to be reversible after delivery. Matrix metalloproteinases (MMPs) and their regulators are connected to periodontal inflammation and destruction. However, the presence and role of the salivary MMPs in pregnancy-related inflammatory destruction are not well known. This study was aimed to evaluate salivary levels matrix metalloproteinase-8 (MMP-8), matrix metalloproteinase-9 (MMP-9) and periodontal status changes during pregnancy. Salivary samples were collected from 30 pregnant women and 30 non-pregnant women. The periodontal examinations included probing pocket depth (PPD), clinical attachment level (CAL), plaque score (PS), and gingival bleeding index (GBI) measurements. MMP-8 and MMP- 9 levels were measured by ELISA and association of salivary MMP-8 and MMP-9 with periodontal parameters of pregnant group was also evaluated. The results of this study showed that the salivary concentrations of MMP-8 and MMP-9 were significantly lower in pregnant women as compared to non-pregnant women. MMP-8 levels were 0.19 ng/ml and MMP-9 levels were 1.57 ng/ml in pregnant women while the MMP-8 and MMP-9 levels in non-pregnant women were 0.34 ng/ml and 2.09 ng/ml respectively. The periodontal parameters in pregnant women were significantly elevated as compared to non-pregnant women. The mean PPD, PS and GBI in pregnant women were 4.38mm ± 0.82, 49.7% ± 13.72 and 47.5% ± 12.90 respectively whilst in non-pregnant were 4.16 ± 0.22, 37.4 ± 18.07 and 35.4 ± 14.50 respectively. Our study concluded that all periodontal parameters were elevated, while salivary inflammatory marker MMP-8 and MMP-9 levels remained low in pregnant group as compared to non-pregnant group and there was no association found between periodontal parameters and salivary levels of MMP-8 and MMP-9 of pregnant women.